An institutional analysis of the International Trade Administration Commission of South Africa - Fiona Tregenna; Marko Kwaramba (Journal of Economic and Financial Sciences, 2014)
This article analyses the role and capacity of the International Trade Administration Commission of South Africa (ITAC), focusing on ITAC’s tariff investigation function. ITAC’s institutional setting is compared to that in other developing countries. An assessment of legal challenges to ITAC decisions shows that the proportion of ITAC’s decisions overturned by the courts has declined over time, suggesting increased robustness of these decisions. ITAC’s current human resources and capacity-building are reviewed. Key institutional issues are discussed and policy recommendations put forward concerning: the appropriate institutional location for tariff-investigations; the current positioning of ITAC under two departments; co-operation between ITAC and other institutions; the strengthening of reciprocity commitments; the role and capacity of part-time Commissioners; the duration of tariff investigations; joint capacity-building among the economic regulators; the extent to which research at ITAC should be undertaken in-house; economics and inspections capacity at ITAC; and the grading of positions at ITAC.